The Influence of Current Ratio, Net Profit Margin, and Debt to Equity Ratio on Profit Changes in Technology Sector Companies - Edo Revaldo; Mariyam Zanariah; Veny Mayasari; Rudi Chairudin (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study analyses the impact of Current Ratio, Net Profit Margin, and Debt to Equity Ratio on the change in profits on companies in the technology sector listed on the Indonesian Stock Exchange. (BEI). Annual financial data of a number of companies were taken for the last few years, namely 2020-2022, and analyzed using regression methods. The results show that Current Ratio and Net Profit Margin have a significant positive relationship to profit changes, suggesting that the company's ability to manage liquidity and operational efficiency contribute to profit performance. On the contrary, Debt to Equity Ratio shows an uninfluential and significant relationship, indicating that the corporate debt level can influence profit changes. The implications of these findings can help financial managers and investors to make more informed decisions in managing risk and improving corporate financial performance in Indonesian capital markets.